The Implementation of a Smart Energy System with IoT Concept for River Water Distribution Pumps in Rainfed Agricultural Areas - Ainul Bashir, Nur Azmi; Bayu Taruno, Restiadi; Hendriana, Yana; Zahrotul Hasanah, Labibah (International Journal of Artificial Intelligence & Robotics (IJAIR), 2024)
Water pumps for irrigating rainfed rice fields are typically located near or at the edge of rivers, for example, in several locations in Bulakelor and Luwunggede, Brebes Regency villages. Similar situations are found in some rice fields in Sendangadi, Mlati, Sleman, and Piyungan, Bantul, where irrigation pumps are near or at the edge of rivers. According to residents, this reduces the suction power needed. Unfortunately, this also affects the terrain, making it damp and the roads muddy and even slippery, which makes the journey to the pump location difficult and risky, like slipping into a river when the ground is wet and slippery. There is a need to solve this problem by creating an automated pump system that implements IoT concepts using microcontrollers and other control components. The manual water pump is replaced with an electric pump to simplify operation. Control is carried out remotely using a mobile application accessible via websites or smartphones, allowing users to monitor pump operations such as usage duration, automatic on/off scheduling, pump status, and more. This reduces the risk of work accidents with the conventional system. A Renewable Energy System (RES) using a solar power plant (PLTS) is also applied to anticipate power outages, ensuring the IoT system continues to operate and irrigation remains manageable. The operation of such pumps still uses conventional methods that require direct human labor, and only specific individuals can operate the pumps. One example is using diesel pumps that are started by cranking, which requires significant physical strength. These pumps are typically managed collectively by the residents, who take turns operating the pump. Another factor is the age of the pump engine itself, which affects its lifespan. The usage is often not well controlled, with uncertainty in the operating times and operator negligence, such as forgetting to turn off the pump. The limitation of this research is that the operation is conducted automatically based on previous pump usage data, ignoring the size of the pipes used in irrigation and focusing on simplifying the operation of the water pump. The system was installed in rainfed fields in Pagergunung hamlet, where farmers used it to operate water pumps via smartphones with the Ubidots application installed and logged in. The results showed that two farmer groups found the automated pump system helpful. The system was built with several components, including the ESP8266 microcontroller, a rain sensor, a relay/power switch, and other supporting components. The system operates automatically according to the morning operational schedule, and operators from each farmer group can control the pump remotely. The pump operates automatically at 6:00 AM, 6:30 AM, and 7:00 AM. If the rain sensor does not detect water drops/rain, the pump will typically run for 1.5 hours. The innovation in this research lies in implementing an automated pump system that operates according to a schedule while allowing remote control of the pump to irrigate rainfed fields.